Suicide squad [videorecording (DVD)] - Ayer, David; Smith, Will, 1968-; Leto, Jared, 1971-; Robbie, Margot, 1990- (Warner Bros. Home Entertainment, 2016)
U.S. intelligence officer Amanda Waller has determined that only a secret group of despicable individuals with nothing to lose can avert a potential apocalypse. So, she has assembled the world's most dangerous super villains, given them a powerful arsenal of weapons, and sent them off on a suicide mission.